Impact of Long-Term Endurance Training vs. Guideline-Based Physical Activity on Brain Structure in Healthy Aging - Wood, Katelyn N.; Nikolov, Robert; Shoemaker, J. Kevin (Frontiers in Aging Neuroscience, 2016)
Brain structure is a fundamental determinant of brain function, both of which decline with age in the adult. Whereas short-term exercise improves brain size in older adults, the impact of endurance training on brain structure when initiated early and sustained throughout life, remains unknown. We tested the hypothesis that long-term competitive aerobic training enhances cortical and subcortical mass compared to middle to older-aged healthy adults who adhere to the minimum physical activity guidelines. Observations were made in 16 masters athletes (MA; 53 ± 6 years, VO2max = 55 ± 10ml/kg/min, training > 15yrs), and 16 active, healthy, and cognitively intact subjects (HA; 58 ± 9 years, VO2max = 38 ± 7ml/kg/min). T1-weighted structural acquisition at 3T enabled quantification of cortical thickness and subcortical gray and white matter volumes. Cardiorespiratory fitness correlated strongly with whole-brain cortical thickness. Subcortical volumetric mass at the lateral ventricles, R hippocampus, R amygdala, and anterior cingulate cortex, correlated with age but not fitness. In a region-of-interest group-based analysis, MA expressed greater cortical thickness in the medial prefrontal cortex, pre and post central gyri, and insula. There was no effect of group on the rate of age-related cortical or subcortical decline. The current data suggest that lifelong endurance training that produces high levels of cardiorespiratory fitness, builds cortical reserve early in life, and sustains this benefit over the 40-70 year age span. This reserve likely has important implications for neurological health later in life.